How to Best Develop and Deliver Generic Long-Term Condition Rehabilitation Programmes in Rural Settings: An Integrative Review - Amanda Wilkinson; Chris Higgs; Tim Stokes; Jack Dummer; Leigh Hale (Frontiers Media S.A., 2022)
People living rurally frequently experience health disparities especially if living with a long-term condition (LTC) or multi-morbidity. Self-management support is a key component of LTC management and commonly included in rehabilitation programmes to enhance ability to self-manage health and encourage physical activity. Such programmes are however often condition focussed and despite evidence for their effectiveness, are not always feasible to deliver in rural settings. Generic programmes are arguably more optimal in the rural context and delivery can be face to face or remotely (via telehealth). The aim of this explorative integrative review was to collate and present international evidence for development, delivery, integration, and support of community-based, generic LTC group rehabilitation programmes delivered rurally in person, or remotely using telehealth. Electronic databases were systematically searched using MeSH terms and keywords. For inclusion, articles were screened for relevance to the aim, and practical information pertaining to the aim were extracted, charted, and organized deductively into themes of Development, Delivery, Integration, and Support. Within each theme, data were synthesized inductively into categories (Theory, Context, Interpersonal aspects, and Technology and Programme aspects). Fifty-five studies were included. Five studies contributed information about community based programmes delivered via the internet. Development was the only theme populated by information from all categories. The theme of Support was only populated with information from one category. Our review has drawn together a large body of diverse work. It has focused on finding practical information pertaining to the best ways to develop, deliver, integrate, and support a community-based generic rehabilitation programme for people living with long-term health conditions, delivered rurally and/or potentially via the internet. Practical suggestions were thematically organized into categories of theory, context, interpersonal aspects, and technology and programme aspects. While the findings of this review might appear simple and self-evident, they are perhaps difficult to enact in practice.